Incubadora social – Sapucaia do Sul: qualificação da política pública de promoção de trabalho e renda - Baioto, Antônio Rafael (Universidade do Vale do Rio dos Sinos, 2021)
We have gone through a lasting scenario of a production crisis and thus unemployment is a reality that afflicts millions of workers. In this scenario, it is worth joining forces in the public and private sectors in order to overcome this situation of business solvency, due to the great difficulty of undertaking. In Sapucaia do Sul, the Municipal Administration developed an alternative to strengthen the local policy to promote the generation of work and income, through the restructuring of the Labor Secretariat, aiming at expanding projects and actions aimed at encouraging entrepreneurship and cooperatives. With this focus, the innovative project for the implementation of a “Cooperative Business Incubator” was developed at the municipal level, which is currently under execution. The Project is an action to promote the generation of work and income that aims to qualify the local policy to promote economic and social development. This research aims to analyze the development of the project and discuss its results, measurable by strengthening the benefited entrepreneurs.
Keywords: Empreendedorismo; Incubadora Social; Economia Solidária; Gestão Pública; Entrepreneurship; Social Incubator; Solidarity Economy; Public Management